Molecular cloning, sequence, expression, and processing of the interleukin 16 precursor - Baier, Michael (The National Academy of Sciences of the USA, 1997)
Interleukin 16 (IL-16) has been shown to function as chemoattractant factor, as a modulator of T-cell activation, and as an inhibitor of immunodeficiency virus replication. The recent identification of inconsistencies in published IL-16 cDNA nucleotide sequences led to the proposal that IL-16 is synthesized in the form of a large precursor protein (pro-IL-16). To identify the true transcriptional start of the IL-16 mRNA rapid amplification of cDNA ends methods were applied. The complete pro-IL-16 cDNA was subsequently molecularly cloned, sequenced, and expressed in COS-7 cells. We report here that pro-IL-16 is most likely synthesized as a 67-kDa protein and is encoded from a major 2.6-kb transcript. Recombinant pro-IL-16 polypeptides are specifically cleaved in lysates of CD8(+) cells, suggesting that the naturally secreted bioactive form of IL-16 is smaller than the originally published 130 amino acids fragment. Moreover, in contrast to other interleukins such as IL-15, IL-16 mRNA expression is almost exclusively limited to lymphatic tissues underlining the potential of IL-16 as an immune regulatory molecule.